2002
DOI: 10.1053/euhj.2001.2694
|View full text |Cite
|
Sign up to set email alerts
|

ST depression in ECG at entry indicates severe coronary lesions and large benefits of an early invasive treatment strategy in unstable coronary artery disease. The FRISC II ECG substudy

Abstract: In unstable coronary artery disease, ST-segment depression is associated with a 100% increase in the occurrence of three-vessel/left main disease and to an increased risk of subsequent cardiac events. In these patients an early invasive strategy substantially decreases death/myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 16 publications
3
37
0
3
Order By: Relevance
“…Therefore, patients presenting with chest pain and ST-segment deviation on ECG were considered to be part of a moderate-to high-risk subgroup, irrespective of other clinical risk factors or initial troponin measurements. This finding is consistent with results from previous studies, which have demonstrated an association between ST-segment depression and adverse prognosis in patients with acute coronary syndromes (24,25). Other independent predictors of 30-day events in our study included male sex, prior acetylsalicylic acid use, history of congestive heart failure and three or more cardiac risk factors.…”
Section: Risk Scoresupporting
confidence: 82%
“…Therefore, patients presenting with chest pain and ST-segment deviation on ECG were considered to be part of a moderate-to high-risk subgroup, irrespective of other clinical risk factors or initial troponin measurements. This finding is consistent with results from previous studies, which have demonstrated an association between ST-segment depression and adverse prognosis in patients with acute coronary syndromes (24,25). Other independent predictors of 30-day events in our study included male sex, prior acetylsalicylic acid use, history of congestive heart failure and three or more cardiac risk factors.…”
Section: Risk Scoresupporting
confidence: 82%
“…Because a widespread use of an early invasive therapeutic strategy in the large and heterogeneous population of patients with non-ST-segment elevation AMI might be costineffective 29,30 or even harmful in those at the lowest risk, 31 identification of the subsets likeliest to benefit from this strategy is a focus of continued attention. 12,13 Accordingly, and in view of its association with severe coronary artery disease, ST-segment elevation in lead aVR could be used, if the results of the present study are confirmed in the large databases now available, as a readily available tool for an early selection of patients for coronary angiography and revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…1 The ECG has been extensively used for this purpose, and ST-segment depression on admission is now recognized as one of the strongest predictors of an adverse outcome. [2][3][4][5][6][7][8][9][10][11] In these patients, ST-segment depression has also been related to the presence of extensive coronary artery disease 3,6,8,12 and to a greater benefit of an early invasive therapeutic approach. 12,13 Lead aVR, whose positive pole is oriented to the right upper side of the heart, usually gives a mirror image of the leads oriented leftward, for which reason it is often ignored.…”
mentioning
confidence: 99%
“…Although evidence supports T‐wave abnormality's adverse prognostic significance,4, 20, 21 our data for the first time indicate that myocardial edema may be the substrate for T‐wave abnormality.…”
Section: Discussionmentioning
confidence: 55%